2022
DOI: 10.1186/s40104-022-00740-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary magnolia bark extract supplementation in finishing pigs on the oxidative stability of meat

Abstract: Background Magnolia bark extract (MBE) is a natural supplement with antioxidant, anti-inflammatory, and antimicrobial activities. Its properties suggest that the dietary supplementation in livestock could improve the quality of products. Therefore, the aim of this study was to investigate, for the first time, the effect of dietary MBE supplementation (0.33 mg/kg) in finishing pigs on the oxidative stability of meat. Oxidative stability is of paramount importance for pork, as it affects storage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…Previous studies showed that the incorporation of magnolol as an additive can have various effects on growth performance. In line with our findings, Menci et al [ 32 ] reported no remarkable effect on growth performance in finishing pigs after dietary supplementation with magnolia bark extract (mainly containing magnolol). Similarly, Xie et al [ 23 ] found that diets supplemented with 100–300 mg/kg of magnolol did not improve the growth performance of yellow-feathered broilers from day 1 to 28, but from day 28 to 51, groups receiving 200 and 300 mg/kg magnolol had higher ADG compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that the incorporation of magnolol as an additive can have various effects on growth performance. In line with our findings, Menci et al [ 32 ] reported no remarkable effect on growth performance in finishing pigs after dietary supplementation with magnolia bark extract (mainly containing magnolol). Similarly, Xie et al [ 23 ] found that diets supplemented with 100–300 mg/kg of magnolol did not improve the growth performance of yellow-feathered broilers from day 1 to 28, but from day 28 to 51, groups receiving 200 and 300 mg/kg magnolol had higher ADG compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Magnolia , a traditional medicinal plant, has been shown to have diverse physiological effects, including mitigation of ROS and lipid oxidation 12 and anti‐inflammatory effects 13 by regulating inflammatory mediators, fatty acid, and cholesterol metabolism 14,15 . Magnolin, derived from Magnolia flos, is shown to exhibit potent therapeutic effects in various inflammatory conditions, such as inflammatory periodontal disease, 16 osteoarthritis, 17 and pulmonary inflammation 18 .…”
Section: Introductionmentioning
confidence: 99%